Essentials for a health service (London : Communist Party, 1946)
1946 1946 1940s 12 pages pulsory. Existing powers under the Factory Medical and Welfare Service Order (1940) could be utilised. The personnel employed in the factory medical inspectorate should be increased in number. Special post-graduate courses in industrial medicine will be necessary. We believe these proposals would be warmly supported by the younger doctors, who would welcome an announcement from you: (1) that you are prepared to arrange the necessary training facilities in the universities, in special hospitals or in suitable local authority hospitals not at present used for teaching; (2) that you intend that the National Health Service shall encourage the participation of doctors in the administrative structure, that medical freedom will not be impaired, and that compensation for capital invested will be available when the buying and selling of practices is stopped (as it must be); (3) that as soon as the report of the Spens Committee is presented, you will state what your attitude is to the question of remuneration, terms of service, etc. Further, we consider that a similar approach can be made to the problem of other health workers, whose services ought to be retained on demobilisation for the development of the National Health Service. 2. The Nursing Problem IT is stated that the present shortage of nurses in the country is over 32,000. We have no data as to the number of nurses employed in the Services nor can we estimate the percentage of those who are likely to return to nursing, but it is highly probable that during demobilisation, and after, there will still be such a degree of shortage as will obstruct the development of the National Health Service. We have put forward the view that the transitional stages towards a comprehensive National Health Service can be organised now so as to facilitate the application of the Bill and also absorb the medical and other health worker staff that is to be demobilised. It will, however, be impossible to carry out the 6 15X/2/103/357